Association of frailty and serum neurofilament light chain levels: the mediating role of estimated glomerular filtration rate - Yang, Wei; Huang, Shan; Xiao, Huanshun; Tao, Pei; Cai, Shuangming (Frontiers in Aging Neuroscience, 2024)
Background: Both frailty and elevated serum neurofilament light chain (sNfL) levels are linked to cognitive impairment. However, evidence of their relationship is lacking, and whether it was mediated by renal function was unknown. This study aimed to investigate the association between frailty and sNfL levels in a representative U.S. population, and to explore the potential mediating role of estimated glomerular filtration rate (eGFR) in this relationship.Methods: Data from 1,782 participants aged 20-75 years in the 2013-2014 National Health and Nutrition Examination Survey (NHANES) were analyzed. Frailty was assessed using a 49-item frailty index, and participants were categorized as non-frail, pre-frail, or frail. sNfL levels were measured using acoustic emission technology. Multivariable linear regression models and restricted cubic spline analyses were employed to examine the associations between frailty, eGFR, and sNfL levels. Mediation analysis was conducted to evaluate the role of eGFR in the frailty-sNfL relationship.The prevalence of pre-frailty and frailty was 45.39% and 11.60%, respectively. A significant positive association was observed between frailty score and sNfL levels (adjusted β: 39.97, SE: 11.07, p=0.003), with a linear relationship confirmed by restricted cubic spline analysis. Frail individuals had significantly higher sNfL levels compared to non-frail participants (adjusted β: 11.86, SE: 5.42, p=0.04). eGFR was negatively associated with sNfL levels (adjusted β: -0.23, SE: 0.05, p<0.001). Mediation analysis revealed that eGFR accounted for 12.52% of the total effect of frailty on sNfL levels (p<0.0001).This study demonstrates a significant association between frailty and elevated sNfL levels in a representative U.S. population, with eGFR partially mediating this relationship. These findings suggest that sNfL may serve as a potential biomarker for frailty-related neuronal damage and highlight the importance of kidney function in this association. Further research is warranted to explore the clinical implications of these findings in frailty assessment and management strategies.